Psychosocial correlates of psychiatric diagnoses and maladaptive behaviour in youth with severe developmental disability. Issue 6 (13th April 2016) - Weiss, J. A.; Ting, V.; Perry, A.
Abstract: Background: We know little about the correlates of mental health problems in youth with severe and profound intellectual disability (ID), as most research includes these youth within larger samples that include greater proportions of mild and moderate disability. The purpose of the current study was to identify the child, family and psychosocial characteristics that were associated with the presence of psychiatric diagnoses and maladaptive behaviour in youth with severe ID. Methods: Participants were 141 parents of youth with severe or profound levels of ID, 4 to 18 years of age. The mean age of children was 11.04 years ( SD = 3.38), with 68% male and 39% with autism spectrum disorder (ASD). Parents completed a primarily online survey of child and family characteristics, negative life events, family quality of life and their own mental health. Results: Logistic regression analyses revealed that youth with a psychiatric diagnosis had higher levels of adaptive behaviour and experienced more negative life events than youth without psychiatric diagnosis, while the presence of clinically significant maladaptive behaviour was related to higher levels of adaptive behaviour, parents' mental health problems and lower family quality of life. Child age, gender, ASD status and financial hardship were not related to either outcome variable. Conclusions: Youth with severe and profound ID who experience psychosocial stressors are more likely reported to have mental health problems than youth without such stressors. It is likely that a combination of child and family based interventions, along with with policies that address larger systemic issues of social adversity, are needed to promote mental health and treat psychopathology when it arises.